A clash at the petri dish: transferring embryos with known genetic anomalies. Issue 2 (7th August 2018) - Daar, Judith
Abstract: Advancing technologies in genetic testing of preimplantation embryos enable IVF patients to access detailed information about their future child's health status, facilitating and complicating their reproductive decision-making. Testing for embryonic genetic anomalies linked to future health has grown increasingly sophisticated. A patient's decision to seek transfer of a health-affected embryo may or may not be compatible with her physician's professional conscience, potentially resulting in a clash at the petri dish. This article sets out arguments in support of physician decisions to assist or decline to assist in the transfer of anomalous embryos upon patient request. Arguments in support of transfer include the preeminence of a patient's reproductive liberty, the value of equal protection as applied to pre- and post-implantation embryos, the allocation of dispositional authority over embryos, and the frailties of predicting a child's future health experience. Arguments that bolster a provider's decision to decline requests for transfer include the role of physician autonomy in the doctor-patient relationship, the theories of reproductive non-maleficence and procreative beneficence, and legitimate concerns over future legal liability. Regardless of a clinic's ultimate position, this article advocates that providers create or adopt detailed policies setting forth their preferences and practices regarding anomalous embryo transfer.